2022
DOI: 10.1186/s12864-022-09045-y
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of the long non-coding RNAs and circular RNAs of the abdominal fat tissues in the chicken lines divergently selected for fatness

Abstract: Background Excessive deposition of abdominal fat poses serious problems in broilers owing to rapid growth. Recently, the evolution of the existing knowledge on long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) have established their indispensable roles in multiple physiological metabolic processes, including adipogenesis and fat deposition. However, not much has been explored on their profiles in the abdominal fat tissues of broilers to date. In the study, we aimed to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In addition, the TGFB2 T (−640) > C SNP was associated with growth and body composition traits in a broiler chicken [46]. As a member of the fibroblast growth factor (FGF) gene family, FGF1 plays a role in adipocyte differentiation and adipose tissue remodeling [47]. In chickens, FGF1 gene expression is positively correlated with intramuscular fat content in male thigh muscle but showed a negative correlation in female birds [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TGFB2 T (−640) > C SNP was associated with growth and body composition traits in a broiler chicken [46]. As a member of the fibroblast growth factor (FGF) gene family, FGF1 plays a role in adipocyte differentiation and adipose tissue remodeling [47]. In chickens, FGF1 gene expression is positively correlated with intramuscular fat content in male thigh muscle but showed a negative correlation in female birds [48].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short noncoding RNAs of approximately 22 nucleotides that negatively regulate gene expression at the posttranscriptional level by recognizing the 3′ UTR of a target mRNA [ 12 14 ]. Studies have shown that miRNAs are involved in regulating various biological processes, including lipid metabolism, adipogenesis, cell proliferation and cell differentiation [ 15 17 ]. For instance, miR-33a inhibits the differentiation of bovine preadipocytes through the IRS2-Akt pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%